Pengaruh Customer Relationship Management (CRM) dan Promosi terhadap Loyalitas Pelanggan XL Axiata - Choirulloh, Alif; Waruwu, Ariyanti Martina; Prastowo, Bagas; Telaumbanua, Pasrah; Yulianto, Yulianto (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Customer Loyalty is one of the challenges for telecommunication companies, including XL Axiata. In a highly competitive industry, companies need to implement effective strategies to maintain customer loyalty. Two strategies that can be adopted are Customer Relationship Management (CRM) and promotion. CRM helps companies build long-term relationships with customers, while promotions drive loyalty and increase customer engagement. This study aims to explore the role of these two factors in increasing customer loyalty at XL Axiata. Data was collected through questionnaires distributed to students of Pamulang University Management Study Program who are XL Axiata customers. The results showed that CRM has no significant effect on customer loyalty, while proper promotion can significantly increase customer loyalty.